Differential Interactions of Flavonoids with the Aryl Hydrocarbon Receptor In Silico and Their Impact on Receptor Activity In Vitro - Monique Reis de Santana; Ylanna Bonfim dos Santos; Késsia Souza Santos; Manoelito Coelho Santos Junior; Mauricio Moraes Victor; Gabriel dos Santos Ramos; Ravena Pereira do Nascimento; Silvia Lima Costa (MDPI AG, 2024)
The molecular mechanisms underlying the observed anticancer effects of flavonoids remain unclear. Increasing evidence shows that the aryl hydrocarbon receptor (AHR) plays a crucial role in neoplastic disease progression, establishing it as a potential drug target. This study evaluated the potential of hydroxy flavonoids, known for their anticancer properties, to interact with AHR, both in silico and in vitro, aiming to understand the mechanisms of action and identify selective AHR modulators. A PAS-B domain homology model was constructed to evaluate in silico interactions of chrysin, naringenin, quercetin apigenin and agathisflavone. The EROD activity assay measured the effects of flavonoids on AHR's activity in human breast cancer cells (MCF7). Simulations showed that chrysin, apigenin, naringenin, and quercetin have the highest AHR binding affinity scores (−13.14 to −15.31), while agathisflavone showed low scores (−0.57 and −5.14). All tested flavonoids had the potential to inhibit AHR activity in a dose-dependent manner in the presence of an agonist (TCDD) in vitro. This study elucidates the distinct modulatory effects of flavonoids on AHR, emphasizing naringenin's newly described antagonistic potential. It underscores the importance of understanding flavonoid's molecular mechanisms, which is crucial for developing novel cancer therapies based on these molecules.